Sistema de gestão ambiental (SGA): Uma aplicação na reciclagem de papel com fibra de bananeira - Barauna, Debora; Anselmo, Juliana Silveira; Stafford, Fernanda do Nascimento; do Amaral, Marcos; Pezzin, Ana Paula Testa; Silva, Denise Abatti Kasper [UNESP] (My University, 2011)
The aim of this study was to examine the effect of environmental management system (EMS) in the production of composites of recycled handmade paper with banana-fibers, adopted by Bastianello (2005), to achieve better environmental and economic performance in the process and develop a product with greater persuasion on the concept of sustainability. The method used was the PDCA, recommended by ABNT NBR 14001:2004. From this it was possible to define a new flow to the process, which provides: control of inputs and raw materials; reduction in water consumption; proposal for reuse of effluent generated; restrictions on the use of chemicals, reduction the influence of individuals in the application of the technique and determination of a minimum mass possible of raw materials to be brought into the process, considering economic and environmental aspects. What we observed was that the new flow, reducing the consumption of water by this process, it also reduced the cost of production, can be said that it was possible to produce more with fewer and better.
Environmental management system (EMS): An application the production of composites of recycled handmade paper with banana-fibers
Keywords: Banana-fibers; Environmental management system; Recycling; Sustainability; Waste paper